(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Dear Editor, Computer vision syndrome (CVS) is defined as complex eye discomfort and vision problems associated with prolonged exposure to digital screens.1 Symptoms include headache, dry eyes, eye strain, blurring of vision, and ocular discomfort after prolonged exposure to light from computers.2,3 Blue light filtering lenses can be used to minimize CVS.2 Globally, around 70 million workers are at risk for computer vision syndrome which reduces the quality of life and work productivity.1 In the western world, use of computers, for both vocational and non-vocational activities, is almost mandatory.1 In today’s COVID-19 (Corona-Virus Disease - 2019) era, use of computers and other digital screen devices is surging in Nepal as well, especially for online study and work from home to control the further spread of coronavirus. Moreover, the lockdown and shutdown done for the virus control by minimizing human gathering increase the demand for virtual learning and working through the online medium.